(untitled) (Journal of Educational Sciences, 2016)
Annotation. The article considers the problems of motivation of undergraduates to learning and fundamental knowledge in professional education. The structure of the article includes consideration of issues: introduction, traditional and innovative model of educational program of magistracy; the practice of self study undergraduates; model to improve teaching and research motivation undergraduates, conclusion. In the innovation model of the educational programs, the emphasis is on andragogic and didactics of teaching adults. A sociological study of undergraduates shows a high level of educational motivation of only 56% of the students, a weak level of 36%. More motivated were graduate students of technical specialties (70%). Revealed stereotypical view the perceived themselves students of a bachelor degree – «bachelor of as unfinished higher education». It can be stated that, despite the nearly 10 years of experience with the implementation of the three cycles of learning, public consciousness is not changed the attitude towards the preparation of the bachelor. At the same time found that 78% of undergraduates consider bachelor – completed higher education, and a master’s degree more complex professional education with the specifics of the analytical and research activities. The suggested model, improving the educational and research students, ‘motivation, based on the principles of systematic, subjectivity, humanization, active and competent approaches. The model includes practical areas of training masters – motivation, competences, value-meaning, activity. One of the Central places in the model takes training development of training and research motivation of the students. According to the survey, the author of the article formulates the recommendations that can be used to conduct trainings among the undergraduates, and also to develop their motivation for learning.